Answer:
a) x = 62
b) x = 33
Explanation:
Hi there!
a) Let´s write the equation:
√(2x-3) = 11
Square both sides
2x - 3 = 121
add 3 to both sides of the equation
2x = 124
divide by 2 both sides
x = 62
Let´s check:
√(2x-3) = 11
x = 62
√(2(62)-3) = 11
√(124-3) = 11
√121 = 11
11 = 11
x = 62 satisfies the equation
b) Let´s write the equation:
∛(6 - x) = -3
Cube both sides
6 - x = -27
subtract 6 to both sides
-x = -27 - 6
-x = -33
divide by -1 both sides
x = 33
Now, let´s check the result:
∛(6 - x) = -3
x = 33
∛(6 - 33) = -3
∛(-27) = -3
-3 = -3
x = 33 satisfies the equation